High burden of RSV hospitalization in very young children: A data linkage study - Homaira, N.; Oei, J.; Mallitt, K.; Abdel-Latif, M.; Hilder, L.; Bajuk, B.; Lui, K.; Ferson, M.; Nurkic, A.; Chambers, G.; Rawlinson, W.; Snelling, Thomas; et al. (Cambridge University Press, 2016)
© Cambridge University Press 2016. Linked administrative population data were used to estimate the burden of childhood respiratory syncytial virus (RSV) hospitalization in an Australian cohort aged < 5 years. RSV-coded hospitalizations data were extracted for all children aged < 5 years born in New South Wales (NSW), Australia between 2001 and 2010. Incidence was calculated as the total number of new episodes of RSV hospitalization divided by the child-years at risk. Mean cost per episode of RSV hospitalization was estimated using public hospital cost weights. The cohort comprised of 870 314 children. The population-based incidence/1000 child-years of RSV hospitalization for children aged < 5 years was 4·9 with a rate of 25·6 in children aged < 3 months. The incidence of RSV hospitalization (per 1000 child-years) was 11·0 for Indigenous children, 81·5 for children with bronchopulmonary dysplasia (BPD), 10·2 for preterm children with gestational age (GA) 32-36 weeks, 27·0 for children with GA 28-31 weeks, 39·0 for children with GA < 28 weeks and 6·7 for term children with low birthweight. RSV hospitalization was associated with an average annual cost of more than AUD 9 million in NSW. RSV was associated with a substantial burden of childhood hospitalization specifically in children aged < 3 months and in Indigenous children and children born preterm or with BPD.